ISOTOPE AND POTENTIAL-ENERGY SURFACE EFFECTS IN VIBRATIONAL BONDING - Clary, D; Connor, J (1984)
Variational calculations of vibrational energy levels have been carried out in order to study vibrational bonding for the IXI and BrXBr molecules with X = Mu, H, and D. Extended London-Eyring-Polanyi-Sato (LEPS) and three-center diatomics-in-molecules (DIM) potential energy surfaces have been used for IXI. For BrXBr, a three-center DIM potential surface was employed. The LEPS surface is purely repulsive, whereas the DIM potentials possess two van der Waals minima. The variational calculations use the exact Hamiltonian of Watson and provide rigorous upper bounds to the energy levels. Calculations have been performed both for the collinear configurations of the atoms as well as in three dimensions, with the total angular momentum quantum number equal to zero. The bond energies of YXY, where Y = Br and I, increase in the order D < H < Mu. This inverse isotope effect is opposite to that for conventional chemical bond energies. The bond energies for IXI also show a sensitive dependence on the nature of the potential surface. The presence of van der Waals wells as well as the lower barrier of the DIM surface increases the number of vibrationally bound states for IXI compared to the case of the LEPS surface. The accurate variational eigenenergies have also been approximately partitioned into normal-mode symmetric, bending, and asymmetric contributions. For all nine systems the symmetric frequency is less than the bending frequency, unlike the case for conventional triatomic molecules. The isotopic dependence of the normal-mode frequencies is consistent with the predictions of the valence force field approximation. The calculations are relevant to the experimental detection of vibrational bonds by conventional spectroscopic techniques or by photodetachment spectroscopy. © 1984 American Chemical Society.